STABILITAS FISIK DAN AKTIVITAS KRIM O/W EKSTRAK ETANOLIK RIMPANG TEMU PUTIH [Curcuma zedoaria (Berg.) Roscoe] SEBAGAI TABIR SURYA SECARA IN VITRO - abdul Karim Zulkarnain; Nenden Asriani (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Sunscreen has been developed for years to overcome the negative effects of UV radiation. The aims of this study were to determine the physical stability of Curcuma zedoaria’s o/w cream during 4 weeks storage at room temperature (±28⁰C) and to determine it’s in vitro sunscreen activity. The study’s done by making zedoaria rhizome’s ethanolic viscous extract; determining extract’s sunscreen activity; formulating o/w cream; and determining cream’s sunscreen activity. The result of the study shows that curcuma zedoaria’s ethanolic extract has sunscreen activity as the SPF values of 100, 150, 200, 250, and 300 ppm extract concentrations are 2,96; 4,61; 6,13; 7,64; dan 9,18. Curcuma zedoaria’s o/w cream preparations are stable during 4 weeks of storage time at room temperature (±28⁰C) and is stable in accelerated stability with centrifugation method. The more extract added into cream, it will increase the viscosity and the stickiness of the cream. The study also shows that Curcuma zedoaria’s o/w cream preparations have sunscreen activity as the 10%, 15%, and 20% extract concentration in creams give the SPF values 7,96; 10,49; and 15,98; %TE values 42,07%; 32,63%; dan 16,12%; and %TP values 70,76%; 61,04%; dan 43,25%.